Adiantum Capillus-Veneris L.: A Comprehensive Review of Its Phytochemical Composition, Pharmacological Activities, and Therapeutic Potential - Mayyadah Jaafer; Wafaa Mahood; Mohammed Alyami (Baghdad Journal of Biochemistry and Applied Biological Sciences)
Adiantaceae, distributed extensively over the world from cool temperature zones to hot tropical regions. Adiantum capillus-veneri L. was shown to include triterpenoids, flavonoids, aoleananes, polysaccharides, phenylpropanoids, carotenoids, and alicyclics by chemical analysis, which participate in several medical properties. The alcoholic and aqueous leaf extract was discovered to be efficient against several strains of Gram-positive and Gram-negative bacteria and also have antifungal properties. An analysis of the antioxidant activity, phytochemicals, and component content reveals that Adiantum capillus-veneris leaves are a rich source of molecules that act as scavengers of free radicals. an ethanolic extract of the leaves of Adiantum capillus-veneris was found to inhibit the oxidative damage caused by hydrogen peroxide by increasing antioxidant enzyme levels, such as those of SOD, CAT, Gpx, and glutathione. The ethanolic extract inhibits the NO release and lowers TNF-α levels, and it has anti-inflammatory activity and has shown therapeutic results in ulcerative colitis in rats due to the presence of phenolic components, flavonoids such as rutin and isoquercetin, triterpenoids, and mucilage, all of which exhibit antioxidant and anti-inflammatory properties. The antidiabetic effect may be caused by the presence of tannins and flavonoids. The plant also has wound-healing properties and enhanced angiogenesis. The important role of extract made of ethanol from the aerial part of Adiantum capillus-veneris was reported as anticancer activity against cancer cell lines like breast (A549), lung (A549), and colon (HCT-116). The investigation revealed encouraging suppression of cancer cell growth in vitro for all fractions. The antidiarrheal action of crude extract of dried leaves of Adiantum capillus-veneris was demonstrated in a mouse model. Other properties such as the hypocholesterolemic effect, the effect of anti-testosterone on hair loss, and the urinary tract effect by decreasing colony-forming units and treating urinary tract infections also decrease levels of calcium, phosphorus, and blood urea.